A retrospective analysis for aetiology and clinical findings of 287 secondary amyloidosis cases in Turkey - TUĞLULAR, ZÜBEYDE SERHAN (OXFORD UNIV PRESS, 2002)
Background. Secondary amyloidosis is the most frequent of the various types of systemic amyloidosis, the epidemiology of which is not yet fully known. The aim of our study was to evaluate retrospectively the collective data for the aetiological distribution, clinical findings and approaches to the management of secondary amyloidosis in Turkey. Methods. Data from a simple questionnaire addressing aetiology, and demographic and clinical characteristics of patients with biopsy-proven secondary amyloidosis was retrospectively analysed. Eleven nephrology clinics contributed data for this study. Results. The 11 contributing centres provided a total of 287 cases (102 female, 185 male). The aetiological distribution was as follows: familial Mediterranean fever (FMF) 64%, tuberculosis 10%, bronchiectasis and chronic obstructive lung disease 6%, rheumatoid arthritis 4%, spondylarthropathy 3%, chronic osteomyelitis 2%, miscellaneous 4%, unknown 7%. Oedema accompanied by proteinuria was present in 88% of the cases, hepatomegaly in 17%, and splenomegaly in 11%. The mean systolic and diastolic blood pressures were 115 +/- 26 and 73 +/- 15 mmHg respectively. The family history was positive in 16%; 73% of the cases were on colchicine treatment when the questionnaire was administered. Thirty-eight per cent of the cases had progressed to ESRD and were on renal replacement therapy. Conclusions. FMF is the leading cause of secondary amyloidosis in Turkey, followed by tuberculosis. Oedema accompanied by proteinuria is the most prominent presenting finding, and hypotension seems to be common among these patients.
Keywords: aetiology; amyloidosis; clinical findings; end-stage renal disease; family history; RENAL AMYLOIDOSIS; COLCHICINE